Exploring DNA methylation profiles in the pathogenesis of human osteoporosis via whole-genome bisulfite sequencing - Yinyin Zhang; Guoying Wu; Jialu Hou; Yeling Zhong; Yukai Zhang; Shishuo Xiong; Zehua Guo; Ying Li (PLoS ONE, 2026)
Osteoporosis is a widespread metabolic bone disorder characterized by diminished bone mass, deteriorated microarchitecture, and increased bone fragility, resulting in elevated fracture risk. This condition adversely affects quality of life and is associated with higher mortality. Growing evidence indicates that DNA methylation serves as a key epigenetic mechanism regulating bone metabolism-related gene expression and may thereby influence osteoporosis pathogenesis. However, the specific relationship between DNA methylation and osteoporosis remains to be fully elucidated. In this hypothesis‑generating pilot study, we demonstrated significant differences in both the extent and distribution of DNA methylation between osteoporosis patients and non‑osteoporosis controls, with notable enrichment in CpG islands. Enrichment analyses based on GO and KEGG pathways revealed distinct biological processes and signaling pathways associated with osteoporosis. Importantly, we identified six genes (MSX1, HOXD4, AXIN2, WNT5A, TGFB1, STAT3) showing directionally consistent methylation‑expression trends, although the DMRs for most genes were located in non‑promoter regions (TTS, exons, introns). After adjusting for the imbalance in sequencing depth, the same directional trends were retained; however, the differences did not reach adjusted statistical significance (median adjusted P > 0.05), likely due to the limited sample size. These genes therefore represent prioritized candidates for exploratory follow‑up in larger, cell‑type‑resolved cohorts. This study provides new insights into the epigenetic mechanisms underlying osteoporosis and highlights potential targets for further investigation.